(untitled) (Annals of Medical Research, 2024)
Aim: Multiple processes have been demonstrated to elucidate the biological toxicity of mercuric chloride, among which oxidative stress has been identified as a contributing factor. The superoxide radical has the potential to induce peroxidation of lipid membranes, alter the activities of proteins and antioxidant enzymes, and modulate gene transcription. Additionally, it has the ability to swiftly deactivate nitric oxide, resulting in impairment of endothelial function and causing harm to macromolecules, membranes, and DNA by generating more harmful radicals including peroxynitrite and hydroxyl radicals. The formation of nitrotyrosine occurs through the interaction between peroxynitrite and tyrosine residues found in proteins. Nitrotyrosine serves as a useful marker for assessing the possible cytotoxic impacts of nitric oxide. While there have been previous animal tests undertaken, the existing literature we have reviewed does not provide evidence regarding the impact of direct mercury exposure and mercury toxicity on nitrotyrosine and nitric oxide. In order to achieve our research objectives, we have devised a plan to investigate the presence of nitrotyrosine and nitric oxide in the blood serum of children who have been exposed to mercury in our study. Materials and Methods: Our study included 65 patients, 42 girls and 23 boys, who had accidentally come into contact with mercury in the laboratories of some schools in Kahramanmaraş, and whose blood mercury level was over 10 μg/l and/or whose urine mercury level was over 15 μg/l. The control group of the study included a total of 23 children, 17 girls and 6 boys, who applied to the pediatric clinic with various complaints, without intoxication or neurological findings, and from whom blood samples would be taken for different diagnoses. Results: Nitric oxide and nitrotyrosine levels were found to be higher in children exposed to mercury than in the control group (p<0.01). Nitric oxide, nitrotyrosine and mercury levels in the patients were high in both genders, and no gender-related difference was detected (p>0.05). The mean duration of mercury exposure was 45 minutes. Of the 65 patients, 20 were asymptomatic and 40 were symptomatic. The most common symptoms were headache and nausea. Conclusion: The existing body of research predominantly focuses on investigating the association between mercury poisoning and oxidative stress biomarkers through animal studies, with a limited number of studies conducted on human subjects. Our study has made a valuable contribution to the existing literature by successfully detecting elevated levels of nitric oxide and nitrotyrosine in children who have been diagnosed with mercury poisoning.